1998
DOI: 10.1002/(sici)1096-9071(199812)56:4<359::aid-jmv12>3.0.co;2-9
|View full text |Cite
|
Sign up to set email alerts
|

Detection of varicella-zoster virus DNA in peripheral mononuclear cells from patients with Ramsay Hunt syndrome or zoster sine herpete

Abstract: On the basis of alterations in varicella-zoster virus (VZV) antibody titers, it appears that Bell's palsy in some patients could be associated with VZV reactivation, that is, zoster sine herpete. To obtain stronger evidence of this association, polymerase chain reaction (PCR) was used to detect VZV DNA in auricular lesions or peripheral blood mononuclear cells (PBMCs) from Bell's palsy or Ramsay Hunt syndrome patients. VZV DNA was detected in the auricular lesions of Ramsay Hunt syndrome, in PBMCs from 2 Ramsa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
2

Year Published

2007
2007
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(9 citation statements)
references
References 18 publications
0
7
0
2
Order By: Relevance
“…Other rare complications include jugular foramen syndrome [440] and non-facial neuromotor deficits [441]. In addition to Ramsay Hunt syndrome, zoster sine herpete is increasingly recognised as a major aetiologic factor in idiopathic Bell’s palsy [442444] and Ménière's disease [445, 446]. …”
Section: Complicating Presentations and Disease Associationsmentioning
confidence: 99%
“…Other rare complications include jugular foramen syndrome [440] and non-facial neuromotor deficits [441]. In addition to Ramsay Hunt syndrome, zoster sine herpete is increasingly recognised as a major aetiologic factor in idiopathic Bell’s palsy [442444] and Ménière's disease [445, 446]. …”
Section: Complicating Presentations and Disease Associationsmentioning
confidence: 99%
“…Furthermore, in 6 of 32 (19%) patients with isolated peripheral facial palsy who had a 4-fold rise in serum antibody to VZV, geniculate zone skin scrapings from 4 of those 6 patients were positive for VZV DNA [8]. Terada et al [9] also found that blood MNCs from 4 of 17 “Bell's palsy” patients were positive for VZV DNA. Although VZV DNA was not found in our patient's saliva, again most likely because saliva was not sampled until one month after the onset of facial palsy, early examination of saliva found VZV DNA in 20% of 10 [10] and 33% of 30 patients [11] with idiopathic peripheral facial palsy.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, multiple forms of trigeminal (Easton, 1970; Hevner et al, 2003; Yamada et al, 2003) and facial (Morgan and Nathwani, 1992; Murakami et al, 1998; Terada et al, 1998) distribution zoster as well as polyneuritis cranialis due to VZV (Osaki et al, 1995; Murata et al, 2010) may occur in the absence of rash.…”
Section: Reactivation Of Vzvmentioning
confidence: 99%
“…The inflammatory response in ganglia of these subjects raised the possibility of prolonged viral infection. Further evidence that PHN may be produced by low-level ganglionitis has come from the detection of VZV DNA and proteins in blood MNCs of many patients with PHN (Vafai et al, 1988; Devlin et al, 1992; Mahalingam et al, 1995) and from the favorable response of some PHN patients to antiviral treatment (Terada et al, 1998; Gilden et al, 2003). …”
Section: Neurologic Complications Of Zostermentioning
confidence: 99%